The Influences of Job Satisfaction and Organizational Commitment on Turnover Intention - Evelyn, Tnay; Abg Ekhsan, Abg Othman; Heng, Chin Siong; Sheilla Lim, Omar Lim (Elsevier Ltd., 2013)
This study aims to investigate and find out the influences of job satisfaction and organizational commitment on employee turnover intention in a production industry. There are a total of 85 questionnaires collected from 100 questionnaires that had been distributed at the chosen organization. Demographic characteristics were discussed briefly according to the frequency level and percentage. In addition, both descriptive and inferential statistics were applied to analyze the data obtained. As for inferential statistics, Pearson Correlation Coefficient was used to measure the degree between independent variables with dependent variable in this research. The research findings showed that for the independent variable of job satisfaction with the factors on satisfaction with pay and supervisory support had a low, and negative significant relationship on employees’ turnover intention. However, organizational commitment had no significant relationship towards turnover intention among the employees within the organization.